Análisis de la cartera de crédito y su relación con el crecimiento de las COACS del segmento 4 en Loja. - Puga Gualan, Roberth Eduardo (2023)
COACS savings and credit cooperatives are part of the Ecuadorian financial system and focus mainly on the most vulnerable sectors of society. They use financial intermediation to promote savings, grant loans, and offer financial services to the members excluded from traditional banking. By extending loans, they obtain income that serves to cover their expenses and can also result in a profit known as surplus, which allows them to become economically powerful, making the credit portfolio a fundamental tool for the growth of savings and credit cooperatives, thus increasing their possibilities of reaching more people and new places where they can offer their financial products and services. Therefore, the general objective of this research is to analyze the credit portfolio and its relationship with the growth of segment 4 COACS in the city of Loja during the period 2019-2022. A mixed approach applied as a methodology, which allowed the collection of qualitative and quantitative data to obtain general knowledge about the state of these organizations and, subsequently, techniques used to analyze the financial statements and collect data on the behavior of the loan portfolio, and by applying the profitability and growth indicators corresponding to the PERLAS system, it was possible to obtain information on the increase in assets. The main results show that nonperforming loans are not a problem for these COACS, remaining below 5%. Increases were also identified in areas such as savings deposits, member contributions, institutional capital, and mainly in the granting of loans, reflected in 39% for COAC CACVIL, 32% for COAC COOPFLIZ, and 10% for COAC SOLIDARIA. It has led to a growth in total assets of 34% for COAC CACVIL, 19% for COAC COOPFLIZ, and 12% for COAC SOLIDARIA in the last year analyzed. Finally, the strategies presented seek to improve the management of the COACS.